Financial Liberalization, Bank Market Structure, and Financial Deepening : An Interest Margin Analysis - Sarr, Abdourahmane (IMF Working Papers; Working Paper, 2000)
The paper shows that commercial banks' ability to lower deposit interest rates (market power) can increase deposit mobilization. Interest expenses saved can subsidize and lower fees on checking and branching services and thus help attract deposits. United States data illustrates the financial deepening effect of this market power. Commercial banks' ability to lower deposit interest rates diminishes when their deposits become closer substitutes to nonbank liabilities requiring greater interest rate competition. Lack of bank deposit market power, including through capital account mobility, may lessen financial deepening.